Analysis of Critical Thinking Skills Improvement Through App Inventor-based Learning Media on Sound Wave Topic - Malik, Adam; Munifah Assani, Qorry; Handayani, Wahyuni; Minan Chusni, Muhammad; Yuniarti Suhendi, Herni (KnE Social Sciences, 2024)
This study aims to analyze the improvement of critical thinking skills using learning media development based on App Inventor on sound wave topics. The research was quasi-experimental with a non-equivalent control group design. The research population were students of class XI MIPA in one of the senior high schools in West Java Province. The sampling technique used was random sampling. Class XI MIPA 5 as the experimental class, used App Inventor-based media, and class XI MIPA 2 as the control class used Google Classroom media. The number of students in both categories were 35 each. The research instrument used a critical thinking skill test. The analysis technique uses n-gain and t-independent sample tests. The results showed an increase in students’ critical thinking skills in the experimental class by 0.67 in the moderate category and the control class by 0.46 in the medium type. The results of the t-independent sample test shows the value of tcount?? > ttable ??. Thus, there is a difference in improving students’ critical thinking skills between learning using App Inventor-based media and using Google Classroom media on sound wave topics. Keywords: critical thinking skills, app inventor-based learning, sound wave.